2016
DOI: 10.1088/1361-6668/30/2/025014
|View full text |Cite
|
Sign up to set email alerts
|

Different approaches to generate matching effects using arrays in contact with superconducting films.

Abstract: Superconducting films in contact with non-superconducting regular arrays can exhibit commensurability effects between the vortex lattice and the unit cell of the pinning array. These matching effects yield a slowdown of the vortex flow and the corresponding dissipation decrease. The superconducting samples are Nb films grown on Si substrates. We have studied these matching effects with the array on top, embedded or threading the Nb superconducting films and using different materials (Si, Cu, Ni, Py dots and do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Figure 2 shows that this matching effect is absent. The second finding reported in [46] is that preserving the local order is crucial to achieve matching effects. If the local order is not retained the magnetoresistance minima vanish.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Figure 2 shows that this matching effect is absent. The second finding reported in [46] is that preserving the local order is crucial to achieve matching effects. If the local order is not retained the magnetoresistance minima vanish.…”
Section: Resultsmentioning
confidence: 93%
“…Recently, del Valle et al have reported two interesting findings on commensurability effects in hybrid samples fabricated with arrays in contact with superconducting films [46]. First, periodic roughness in the superconducting film is enough to generate resistivity minima.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that the interstitial sites are not energetically favorable when the magnetic field is tilted beyond this angle and usual commensurability for the first matching field arises. In order to understand this effect, it has to be considered that the potential landscape created by the Nb nanotriangles emerges from both the repulsive potential created by the superconducting character of the nanotriangles, and the attractive one created by the periodic corrugation [21]. Therefore, when the parallel component (H || ) of the applied magnetic field increases, the superconducting performance of the Nb nanotriangles is diminished and the antipinning potential is smoothed.…”
Section: Resultsmentioning
confidence: 99%